PENGGUNAAN SITOSTATIKA PADA PASIEN KANKER DEWASA DI RUANG KEMOTERAPI RSUP FATMAWATI PERIODE BULAN JANUARI SAMPAI JUNI TAHUN 2020 - Niken Oktovina, Magdalena (Jurnal Farmasi Klinik Best Practice, 2022)
Chemotherapy is one of the treatment modalities for systemic cancer which is often chosen, especially to treat advanced, local and metastatic cancers. The administration of cytostatics is carried out in a special room to avoid exposure to cytostatics and for the safety of patients and officers giving cytostatics. The administration of cytostatics is adjusted to the diagnosis of cancer. Therefore, the researcher wanted to know how the use of cytostatics in cancer patients in the Chemotherapy room of Fatmawati Hospital, especially in adult patients. This study aims to determine the characteristics of adult cancer patients who undergo chemotherapy in the chemotherapy room, and the use of cytostatics based on drug class and type, and how the characteristics of adult patients relate to the use of cytostatics. The research method was carried out by taking data from adult patients diagnosed with cancer and administering chemotherapy from January to June 2020 in the chemotherapy room by paying attention to inclusion and exclusion criteria. The results showed 1272 adult patients who administered chemotherapy and 3785 cytostatic preparations from January to June 2020. From the evaluation, it was found that the most cancer patient characteristics based on gender were 78.22% women with an age range of ≥40 - 60 years of 60.14 % and the most disease diagnoses were breast cancer at 50.63%. The use of cytostatics based on group is antimetabolite with pyrimidine analogues (Fuorouracil (5-FU) and Gemcitabine) and folic acid analogues (Methotrexate) with a value of 28.22%. The highest use of cytostatic types was Fluorouracil (5-FU), which was 19.47%. The relationship between patient characteristics and use of cytostatics is in gender, age and indication of drug use (disease diagnosis). The results of this study are very useful considering the scarcity of literature due to the limited implementation units that carry out the provision of sitostatics such as Fatmawati General Hospital. Therefore, it can be suggested for further research related to the relationship between drug use and cancer diagnosis in the context of drug availability and cost analysis, as well as evaluation of the side effects that occur when administering cytostatics through documented interviews with patients. Keyword : Chemotherapy, Sitostatics, Cancer, Fatmawati General Hospital.